The Analysis of The Government Transfer Funds in Affecting The Human Development Index at Autonomous Region - Nurmansyah, Fajar; Tandean, Vivi Adeyani (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2024)
This study aims to assess how the allocation of transfer funds from the Central Government to Local Government impacts the Human Development Index (HDI) across Indonesia’s autonomous regions. The funds analyzed include the Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DTK), Specific Purpose Grants (DAK), Local Incentive Fund (DID), and Village Fund. The study spans from 2017 to 2022, covering six years following a change in budget classification for the Transfer to Local Government fund. Data was primarily sourced from the Directorate General of Fiscal Balance (DJPK) at the Ministry of Finance and the Central Bureau of Statistics (BPS). The analysis employs panel data using the Fixed Effect Model (FEM) to handle cross-sectional and time-series data. Results indicate a significant positive effect of the Special Allocation Fund (DTK), comprising Specific Purpose Grants (DAK) and Local Incentive Fund (DID), on the Human Development Index (HDI) in Indonesia’s autonomous regions, with a p-value below the significance level of 0.05. However, the General Allocation Fund (DAU) shows no significant effect, with a p-value exceeding 0.05. Additionally, the Revenue Sharing Fund (DBH) and Village Fund partially affect the Human Development Index (HDI).